Linhas de inquirição: extraindo informações prejudiciais em entrevistas policiais investigativas com suspeitos na Inglaterra - Almeida, Fábio Ferraz de (Language and Law / Linguagem e Direito, 2020)
In this paper, I focus on showing some features of police questioning in England by describing and analysing episodes in which lines of questioning are constructed by police ocers. I show that in the interviewing model adopted by the police in England, the ocers’ agenda is not to explicitly look for a confession when questioning suspected criminals. Nonetheless, they are still able to elicit information which may undermine the suspects’ version of events. The data consisted of an audio-recorded investigative interview with a teenage suspect accused of having assaulted a colleague in England. This interview has been transcribed and examined using the tools of Conversation Analysis. The paper is organised into two sections: in the first one, I describe how questions in police investigative interviews have a progressive character, i.e. they gradually move from what appears to be an innocent, innocuous or neutral topic to a point at which the police officer reveals – or at least makes more visible to the suspect and therefore for the analyst – his/her project. In the second section, I connect the progressivity of these questions to what seems to be a key project in most of these lines of questioning, that is, police officers are oriented to elicit information from the suspect and build some sort of inconsistency between the evidence they have already collected and what has been stated by the suspect in the interview.